2016
DOI: 10.18553/jmcp.2016.22.5.588
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Persistence in Patients with Severe Major Depressive Disorder with Psychotic Features: Antidepressant and Second-Generation Antipsychotic Therapy Versus Antidepressant Monotherapy

Abstract: Kim-Romo received funding to conduct this study from the PhRMA Foundation Pre-Doctoral Fellowship in Health Outcomes. Rascati, Richards, Ford, Wilson, and Beretvas declare no conflict of interest in relation to this manuscript. Kim-Romo and Rascati collaborated on the study design, data analysis, study interpretation, and writing of this manuscript. Richards, Ford, Wilson, and Beretvas provided critical evaluation of the study design, analysis, and interpretation, as well as edited this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…The results that the mean of the MPR and the LOT increased in patients who continued to receive IP and that females with depression have a higher percentage of adherence and persistence than men is similar to previous studies [ 44 , 45 ]. However, in terms of age groups, an opposite result was observed compared with previous work [ 11 , 22 , 23 ]. The studies of Olfson et al (2006) and Akincigil et al (2007) were measured using patient questionnaires, and in other antidepressant studies, the result of age was interpreted because several factors, such as education and stigma, could be reflected [ 3 , 44 ].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The results that the mean of the MPR and the LOT increased in patients who continued to receive IP and that females with depression have a higher percentage of adherence and persistence than men is similar to previous studies [ 44 , 45 ]. However, in terms of age groups, an opposite result was observed compared with previous work [ 11 , 22 , 23 ]. The studies of Olfson et al (2006) and Akincigil et al (2007) were measured using patient questionnaires, and in other antidepressant studies, the result of age was interpreted because several factors, such as education and stigma, could be reflected [ 3 , 44 ].…”
Section: Discussioncontrasting
confidence: 84%
“…The MPR was defined as the number of days the patient possessed the study medication, divided by the observation period of 180 days [ 20 , 21 ]. An adherent patient was defined as an MPR being more than or equal to 0.8 [ 22 , 23 ]. The LOT, which measures the duration of time from the initiation to the discontinuation of therapy, was defined as the number of days from the index date to the earliest ending date of the last prescription, with the permissible gap being 14 days [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] African Americans (AA) show greater concerns of AD use, less understanding of treatment, and less adherence when compared to non-Hispanic whites. [13][14][15] Hispanic culture's unique barriers, stigma, and beliefs may lead to greater non-adherence to antidepressants. 16,17 For instance, one study found that Hispanic's belief of familismo may be leading to non-adherence.…”
Section: Non-adherence Risk Factorsmentioning
confidence: 99%
“…Antipsychotics augment antidepressants in 12-32% of older adults with depression [3][4][5][6], albeit in most cases in an off-label manner [7]. Antipsychotics contribute not only to treating psychotic symptoms in severe depression with psychotic features [8], but also to depressive symptom improvement, since they enhance monoaminergic neurotransmission [9].…”
Section: Introductionmentioning
confidence: 99%